Guanylylation and adenylylation of the alpha regulatory proteins of herpes simplex virus require a viral beta or gamma function. - Blaho, J A (1993)
Herpes simplex virus genes form several groups whose expression is coordinately regulated and sequentially ordered in a cascade fashion. Most of the products of the first group, the alpha genes, appear to have regulatory functions. We report that the alpha proteins, infected cell proteins 4, 0, 22, and 27 of herpes simplex virus 1 and 4, 0, and 27 of herpes simplex virus 2, were labeled in the isolated nuclei of infected HeLa cells with [alpha-32P]GTP or [alpha-32P]ATP late in infection and that these proteins represent the largest group of virus-specific proteins labeled in this fashion. Studies with [2-3H]ATP, in which the label is in the purine ring, showed that a portion of the label in alpha proteins and in at least one other infected cell protein is due to nucleotidylylation. Analyses of the labeling reactions in nuclei of (i) cells infected with temperature-sensitive mutants at nonpermissive temperatures, (ii) cells infected with wild-type virus and harvested at different times postinfection, and (iii) cells treated with inhibitors of protein synthesis or of synthesis of viral DNA led to the conclusion that viral gene functions expressed after the synthesis of alpha proteins are required for the labeling of the alpha proteins with [alpha-32P]GTP. We conclude that several of the alpha proteins are extensively posttranslationally modified and that these modifications include nucleotidylylation.